2006
DOI: 10.1530/eje.1.02187
|View full text |Cite
|
Sign up to set email alerts
|

Oxidised low-density lipoprotein concentration – early marker of an altered lipid metabolism in young women with PCOS

Abstract: Objective: Women with polycystic ovary syndrome (PCOS) are assumed to be at increased risk for cardiovascular diseases. This study examined the variations in oxidised low-density lipoprotein (OxLDL) concentration in relation to insulin levels in young women with PCOS. Design: Cross-sectional clinical study in tertiary cares research hospitals. A total of 179 women with PCOS (79 overweight) and 56 age-and body mass index-matched controls were examined. Methods: Blood samples were collected in follicular phase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 33 publications
7
44
0
Order By: Relevance
“…These findings are supported by previous studies in PCOS and suggest that the increase in levels of oxLDL in PCOS more closely relates to insulin resistance and abdominal obesity than to hyperandrogenemia (17,19).…”
Section: Il-6supporting
confidence: 89%
See 1 more Smart Citation
“…These findings are supported by previous studies in PCOS and suggest that the increase in levels of oxLDL in PCOS more closely relates to insulin resistance and abdominal obesity than to hyperandrogenemia (17,19).…”
Section: Il-6supporting
confidence: 89%
“…Increased levels of ox-LDL in PCOS patients compared with weight-matched control subjects were documented in a recent study (17) in found comparable oxLDL levels in normal-weight and overweight PCOS patients. These findings suggested a minor association between body weight and oxLDL levels in PCOS and are in agreement with the BMIindependent correlation between oxLDL and glucose and lipid metabolism in the present study.…”
Section: Il-6mentioning
confidence: 77%
“…Several cardiovascular risk factors, including dyslipidemia (7,8), impaired glucose metabolism (9), abdominal obesity (10), and the metabolic syndrome (11), are more prevalent in PCOS women than in the general population and possibly contribute to the greater cardiovascular morbidity and mortality in PCOS. Of note, women diagnosed with PCOS according to the 1990 criteria have more adverse metabolic profile than those diagnosed according to the additional 2003 criteria (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] In addition, it has been reported that oxidized low-density lipoprotein (LDL) which starts the atherogenesis, through foam cell formation and inflammatory responses, were found to be higher in women with PCOS than in controls. 25,26 Contrary to this process; high-density lipoprotein (HDL) shows anti-inflammatory and antioxidant effects. 27,28 Due to its small size (lower than 300 kDa); the permanent of HDL is possible to the FF.…”
Section: Discussionmentioning
confidence: 99%